TRANSACTIONAL LEADERSHIP, MOTIVATION, AND COMPETENCE EFFECTS ON EMPLOYEE PERFORMANCE - Atika, Nur; Reskiputri, Tatit Diansari; Umamy, Septy Holisa (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
Despite advancements in public service reform, employee performance at the Investment and One-Stop Integrated Services Agency in Jember Regency remains inconsistent, marked by delayed service delivery, low initiative, and reduced task effectiveness. This study investigates the influence of transactional leadership, motivation, and competence on employee performance to identify key drivers of organizational efficiency. A quantitative associative method was employed, with data collected from 85 employees via structured questionnaires and analyzed using multiple linear regression. Results indicate that motivation and competence have a significant positive effect on performance (p < 0.05), underscoring their critical role in enhancing productivity and service quality. In contrast, transactional leadership does not show a significant impact, challenging its assumed centrality in bureaucratic settings. The model explains 56% of the variance in performance (R² = 0.56). The originality of this study lies in its empirical examination of leadership limitations in a developing-country public service context, where motivational and competency-based factors outweigh directive leadership in driving performance. It contributes to theory by refining the application of leadership models in local government institutions and offers practical guidance for reforming human resource strategies. Findings suggest that investing in employee development, intrinsic motivation, and skill enhancement is more effective than relying solely on hierarchical supervision.